As-Sirah An-Nabawiah As-Sahihah Jilid I & II - Akram Diya‟ Al-Umari 1993 ([Publisher is not identified], 2013)
A biography of the Messenger of Allah sallallahu alayhi wa sallam, compiled and written by Dr. Akram al-Umary, a specialist in the field, who has used only authentic sources for his book. A detailed and structured biography with no weak narratives, which is recommended by many scholars.